Evaluation of NAVA-PAP in premature neonates with apnea of prematurity: minimal backup ventilation and clinically significant events - Protain, Alison; Firestone, Kimberly; Hussain, Saima; Lubarsky, Daniel; Stein, Howard (Frontiers in Pediatrics, 2023)
Background: Neonates with apnea of prematurity (AOP) deteriorate clinically because CPAP provides inadequate support during apnea. Neurally Adjusted Ventilatory Assist (NAVA) provides proportional ventilator support from the electrical activity of the diaphragm. When NAVA level is 0 cmH20/mcV (NAVA-PAP), patients receive CPAP when breathing and backup ventilation when apneic. This study evaluates NAVA-PAP and time spent in back up ventilation. Methods: Prospective, two center, observational study of preterm neonates on NAVA-PAP for AOP. Ventilator data were downloaded for 24 hours. Number of Clinically Significant Events (CSEs) were collected. Statistics were paired t-test. Results: Twenty-eight subjects with gestational age 25 + 1.8 weeks, study age 28 ± 23 days. CSE were 4±4.39/24 hours. Subjects were on NAVA-PAP approximately 90%/minute, switched to back-up mode 2.5±1.1 times/minute and spent 10.6±7.2% in back-up. Conclusion: Preterm neonates on NAVA-PAP had few clinically significant events with minimal time in back up ventilation.